Pendidikan Karakter Kebangsaan Berbasis Syi’ir Lokal di Pesantren Salafiyah Kapurejo Pagu Kabupaten Kediri - Nailal Nailal Muna (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
Character education is a tradition that has long been implemented in Islamic boarding schools through various media. This study discusses the national character in the tradition of the Salafiyah pesantren, Kapurejo Village, Pagu District, Kediri Regency by using a local curriculum in the form of syi'ir. This curriculum has been implemented since the 1950s. The focus of this research is how to implement the syi'ir tradition, and what national character is obtained by the santri. This research is classified as a qualitative research, with data collection methods of observation, interviews and documentation. Data analysis using data reduction. The results of the study show that the syi'ir education curriculum is carried out in a structured manner, and has not changed. The national character obtained by the students are religious values, independence, democracy, national spirit, and social care